Optimizing Web-Based Survey Applications with Laravel and Cloud Computing - Saputri, Nanda; Safriadi, Safriadi; Dahlia, Zaharatul; Rahmadani, Rahmadani (Yayasan Kita Menulis, 2024)
This study aims to optimize the performance of a web-based survey application through the implementation of the Laravel framework and cloud computing technology. Survey applications often face challenges regarding response speed and scalability as the number of users increases. In this research, performance testing of the application was conducted both before and after optimization. The test results show that the application's response time significantly decreased after the implementation of Laravel and cloud technology. Before optimization, the average response time reached 4.5 seconds at 1,000 users, while after optimization, it dropped to 2.2 seconds. This performance improvement was achieved through efficient caching implementation, database query optimization using Eloquent ORM, and balanced load distribution via load balancers. Additionally, the application's availability increased to 99.9% thanks to cloud features such as auto-scaling and data replication. The conclusion of this study indicates that the combination of Laravel and cloud computing technology is effective in enhancing the performance and reliability of web-based survey applications, providing practical guidance for other web application developers facing similar challenges.